PERAN PENGAWAS MENELAN OBAT DAN STATUS GIZI DALAM MENINGKATKAN KEBERHASILAN PENGOBATAN TUBERKULOSIS - Huwaynan Nysa Djiby; Rita Khairani (Fakultas Kedokteran Universitas Trisakti, 2024)
Tuberculosis (TB) is a highly infectious diseases that can be fatal, similar to COVID-19. Transmission occurs through droplets containing acid-resistant bacteria. TB treatment requires a considerable amount of time. The presence of someone who can monitor and ensure that the patient takes the medication regularly is important. The supervisor responsible for this is also known as the Treatrment Observer (TO), who can be a healthcare worker or a family member. In addition to the TO presence, improving nutritional conditions is also necessary to enhance treatment success rates. Several studies on the relationship between TO and nutritional status with the treatment success rates have produced conflicting results. The objective of this research is to assess the role of TO and nutritional status in treatment success rates. The research method was observational analytics with a cross-sectional approach involving 68 subjects. Data utilized include both primary and secondary sources, with a validated questionnaire used to assess the MAS's role, and nutritional status evaluated by measuring the body mass index. Data analysis employs the Chi-square test with significance set at <0.05.The prevalence of supportive MAS is 77.9%, and the normal nutritional status category is 48.5%. The success rate of TB treatment is 60.3%, with 69.8% of them being supported by the presence of MAS. There is a significant relationship between MAS (p=0.006) and nutritional status (p=0.006) with the success of TB treatment.